Community universities in the South of Brazil: prospects and challenges of a model of non-state public higher education. Issue 3 (3rd July 2018) - Fioreze, Cristina; McCowan, Tristan
ABSTRACT: In recent years, higher education institutions have been encouraged to engage more strongly with their local communities, and address their historically weak links with their surrounding populations. In the latter part of the twentieth century, a number of community universities were established in the South of Brazil, characterised by democratic local community involvement, expansion of access in non-metropolitan regions, and close ties with local industry. This article analyses these innovative institutions in relation to the complex demands of the so-called knowledge economy and multifaceted relationships between public and private, exploring the ways in which the public good role of universities manifests itself in relation to the local. Given their hybrid nature – independent from the state but with a public good mission – these institutions can be seen to represent a new model of non-state public higher education. Implications are drawn out for the potential role of these institutions in the current policy context of Brazil, and internationally, in light of their context-specificity and the significant challenges from the highly commercialised for-profit sector.